Compassionate use of the self‐expandable medtronic corevalve prosthesis for the treatment of pure aortic regurgitation in a patient at prohibitive risk for surgical valve replacement. Issue 7 (9th July 2013) - Hildebrandt, H.A.; Erbel, R.; Kahlert, P.
<x xml:space="preserve">Abstract</x> Transcatheter aortic valve implantation (TAVI) is a viable treatment option for high‐ and prohibitive‐risk patients with severe, calcified pure or predominant aortic valve stenosis, but not for pure aortic valve regurgitation. In fact, the use of TAVI for this indication is even considered unlikely due to the lack of calcium which appears essential for anchoring the stent‐valve and prevents dislocation. We report a case of a patient with severe, symptomatic pure aortic regurgitation, and a history of two previous open‐heart surgeries who was successfully treated by compassionate use implantation of an oversized Medtronic CoreValve prosthesis as an ultima ratio treatment option. © 2012 Wiley Periodicals, Inc.